COMMUNICATIVE APPROACH TO TEACHING ENGLISH - Shukurova Zebiniso Inoyatullayevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The role and importance of the communicative approach in English language education in secondary schools is determined. An approach is a set of concepts related to the characteristics of language teaching and learning. The approach is axiomatic. It represents the content of the taught subject. The term "approach" is defined in dictionaries in the sense that it is based on a certain theory to solve a problem or find a solution to a problem.